2016
DOI: 10.5455/ijmsph.2016.07022016390
|View full text |Cite
|
Sign up to set email alerts
|

Six-year analysis of postmortem examination records at a teaching hospital - demographic profile and causes of deaths

Abstract: Background: Medicolegal postmortem examinations are performed as mandatory legal procedures for establishing the cause of death for people dying in circumstances where multiple causes of death could be ascribed. Objective: To conduct complete-enumeration analysis of demographic details and causes of death from postmortem examination records at a municipal teaching hospital in Thane city, Maharashtra state, India. Materials and Methods: Data recorded on the postmortem records from Jan 1, 2009 to Dec 31, 2014 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…This finding of a preponderance of R.T.A.s amongst medicolegal autopsies is not in agreement with studies reported from some parts of India. 17,18,31 The occurrence of suicidal and homicidal fatalities in our study wascomparable to those in other parts of India 20,29. This was true for cases seen in Norway as well, 29 but not in Great Britain and Libya,where suicides were low and homicidal deaths were greater in Libya, where it was twenty percent as contrasted to our 2.7%. 28 The occurrence of unnatural deaths was quite comparable to trends reported from various parts of India and globally.…”
Section: Discussionsupporting
confidence: 52%
“…This finding of a preponderance of R.T.A.s amongst medicolegal autopsies is not in agreement with studies reported from some parts of India. 17,18,31 The occurrence of suicidal and homicidal fatalities in our study wascomparable to those in other parts of India 20,29. This was true for cases seen in Norway as well, 29 but not in Great Britain and Libya,where suicides were low and homicidal deaths were greater in Libya, where it was twenty percent as contrasted to our 2.7%. 28 The occurrence of unnatural deaths was quite comparable to trends reported from various parts of India and globally.…”
Section: Discussionsupporting
confidence: 52%